Transference Number And Structural Analysis Of Proton Conducting Polymer Electrolyte Based On poly(epsilon-caprolactone) - Majid, Siti Rohana; Arof, Abdul Kariem; Woo, H.J. (Springer Verlag (Germany), 2011)
Poly(e-caprolactone) (PCL) is used as the polymer host to dissociate ammonium thiocyanate (NH(4)SCN). Free standing solid polymer electrolytes of varied weight ratios are prepared by solution casting technique with tetrahydrofuran as solvents. Impedance measurement shows the highest ionic conductivity achieved at room temperature is 1.01 x 10(-4) S cm(-1) for PCL incorporated with 26 wt-% NH(4)SCN. In transference number analysis, the total ionic transference number is calculated to be 0.966 using blocking electrode cell configuration. The value of t(+) is evaluated to be 0.21 using reversible electrode cell configuration. The ohmic portion of steady state current indicates the existence of mobile ion pairs or higher aggregates. In X-ray diffraction analysis, crystalline peaks were deconvoluted from the continuous halo with high goodness of fit. The degree of crystallinity as a function of salt concentration is estimated and is in exact agreement with ionic conductivity variation, concluding that accommodation of salt into the polymer matrix depresses the crystalline phase of PCL.